Aromatic polymer proton exchange membrane and preparation method and application thereof
By introducing polyphenyl fluorone polymeter and fluoride hydrophobic groups in the Fangzu aggregate substance switching membrane, and sulfide treatment, the proportion of hydrophobic sections is controlled, and high -tech rates and good size under high temperature and high humidity conditions are achieved. Stability solves the problem of high costs and difficulty in existing technology.
Patent Information
- Application Number
- CN202211722094.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-12-30
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2042-12-30
AI Technical Summary
The aromatic polymeric substance sub-exchange membrane cannot have high conductivity and good dimensional stability properties under high temperature and high humidity conditions, and the synthesis cost and difficulty are high.
The polyophenyl fluorone polymer is used as the basic skeleton to introduce a fluorine -containing group closer, and sulfate the bromone fluorone chain to control the proportion of the repeated unit of the hydrophobic section is 5 % to 20 % to build an efficient ionic ionic ionic Transmission channel.
Improve the thermal stability, chemical resistance and mechanical properties of the membrane, at the same time enhanced the proton conduction rate and hydrolysis, and solve the problem of the size stability and the conductivity.
Smart Images

Figure CN116253912B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of new energy materials, and in particular to an aromatic polymer proton exchange membrane and a preparation method and application thereof. Background Art
[0002] Proton exchange membrane (PEM, Proton Exchange Membrane or Polymer Electrolyte Membrane), also referred to as proton membrane or acid membrane, plays a key role in many electrochemical devices (such as fuel cells, water electrolyzers, hydrogen pumps, etc.). PEM can not only transfer protons, but also serve as a separator between reaction gases, fuels and electrons. Its performance and durability directly determine the performance and life of the device.
[0003] Currently, perfluorosulfonic acid polyelectrolytes (PFSA) such as Nafion are the most widely used PEM membrane materials due to their commercial availability, good proton conductivity and excellent chemical stability. However, PFSA has disadvantages such as high cost, complex membrane casting process, difficulty in adjusting material properties through chemical modification, and high methanol permeability. Therefore, the development of low-cost, high-performance PEM membrane materials is a difficult problem that needs to be tackled urgently.
[0004] Aromatic polymers are promising alternative materials to PFSAs. They have low synthesis costs and can easily achieve stereo-controllable chemical structures, sulfonation sites, and fine microstructures through grafting, block and random polymerization. In addition, researchers have reported that using fluorinated groups as hydrophobic domains and introducing fluorinated groups can improve the solubility, glass transition temperature, thermal stability, and chemical resistance of polymers, while reducing hygroscopicity and dielectric constant. Therefore, partially fluorinated aromatic PEM membrane materials have become a research hotspot in recent years.
[0005] However, compared to PFSA PEM, aromatic polymer PEMs generally exhibit lower proton conductivity than Nafion, especially under reduced humidity conditions. To compensate for this, hydrocarbon-based PEMs generally have a high ion exchange capacity (IEC) to increase the charge carrier concentration, thereby improving proton conductivity. However, this can lead to excessive water absorption and swelling under high humidity conditions. On the other hand, in order to simultaneously improve the mechanical properties, a multi-structure is compounded, which increases the cost and difficulty of synthesis. Therefore, how to synthesize a PEM that maintains dimensional stability, oxidative stability, and mechanical strength under higher proton conductivity through a simple method is a huge challenge facing the current research and development of aromatic polymer PEMs. Summary of the invention
[0006] In view of this, the present invention provides an aromatic polymer proton exchange membrane and a preparation method and application thereof. The aromatic polymer proton exchange membrane provided by the present invention can improve proton conductivity while maintaining good dimensional stability under high temperature and high humidity conditions, and its synthesis method is simple, which can reduce the difficulty and cost of synthesis.
[0007] The present invention provides an aromatic polymer proton exchange membrane, wherein the membrane material is formed by an aromatic polymer represented by formula (I):
[0008]
[0009] in,
[0010] x, y are the molar percentages of the corresponding repeating units to all repeating units;
[0011] x+y=100%, and y / (x+y)=5%~20%;
[0012] n is the degree of polymerization, n≥10;
[0013] j is an integer from 1 to 6;
[0014] Ar is selected from any one of the structures of formula Ar1 to Ar6:
[0015]
[0016] R is selected from any one of the structures of formula R1 to R3:
[0017]
[0018] In the above formula R1, p is an integer of 0-6.
[0019] Preferably, the aromatic polymer is selected from formula (I-1) to formula (I-6):
[0020]
[0021] The present invention also provides a method for preparing the aromatic polymer proton exchange membrane described in the above technical solution, comprising the following steps:
[0022] a) reacting a precursor of formula (Ia) with potassium thioacetate to form an intermediate of formula (Ib);
[0023] b) mixing the intermediate of formula (Ib) with m-chloroperbenzoic acid and an inorganic salt to form a polymer of formula (Ic);
[0024] c) dissolving the polymer of formula (Ic) in a solvent to obtain a casting solution;
[0025] d) coating the casting solution on a substrate, and subjecting the substrate to a heat treatment to volatilize the solvent to obtain a thin film;
[0026] e) immersing the film in an acid solution to perform ion exchange, and then immersing it in water to remove excess acid solution to obtain a proton exchange membrane containing the aromatic polymer represented by formula (I);
[0027] in,
[0028] The structure of the precursor of formula (Ia) is as follows:
[0029]
[0030] The structure of the intermediate of formula (Ib) is as follows:
[0031]
[0032] The structure of the polymer of formula (Ic) is as follows:
[0033]
[0034] The structure of the polymer represented by formula (I) is as follows:
[0035]
[0036] In the above formula (Ia), formula (Ib), formula (Ic) and formula (I):
[0037] x and y are the molar percentages of the corresponding repeating units in the total repeating units; x+y=100%, and y / (x+y)=5% to 20%;
[0038] n is the degree of polymerization, n≥10;
[0039] j is an integer from 1 to 6;
[0040] Ar is selected from any one of the structures of formula Ar1 to Ar6:
[0041]
[0042] R is selected from any one of the structures of formula R1 to R3:
[0043]
[0044] In the above formula R1, p is an integer from 0 to 6;
[0045] In the formula (Ic), M is Na or K.
[0046] Preferably, in step a), the precursor of formula (Ia) is prepared by the following preparation method: compound Ar', compound R' and compound C react to form a precursor of formula (Ia);
[0047] The compound Ar' is selected from any one of the formulas Ar1' to Ar6':
[0048]
[0049] The structure of the compound R' is shown in formula R':
[0050]
[0051] Wherein, R is selected from any one of the structures of formula R1 to R3:
[0052]
[0053] In the above formula R1, p is an integer from 0 to 6;
[0054] The structure of the compound C is shown in Formula C:
[0055]
[0056] Here, j is an integer from 1 to 6.
[0057] Preferably, the step a) specifically comprises:
[0058] a1) reacting a precursor of formula (Ia) with potassium thioacetate and an organic solvent to obtain a reaction solution;
[0059] a2) Post-treatment: The reaction solution is put into an alcohol solvent for precipitation, followed by solid-liquid separation. Thereafter, the obtained solid-liquid is dissolved in an organic solvent, and then precipitated again with an alcohol solvent and solid-liquid separated to obtain the intermediate of formula (Ib).
[0060] Preferably, the step b) specifically comprises:
[0061] b1) dissolving the intermediate of formula (Ib) in an organic solvent to obtain a solution;
[0062] b2) after cooling the dissolved solution, adding m-chloroperbenzoic acid, then returning to the temperature and stirring evenly to obtain a solution;
[0063] b3) mixing the solution obtained in step b2) with an inorganic salt solution, and then performing solid-liquid separation and washing to obtain a solid;
[0064] b4) dissolving the solid in an organic solvent, precipitating with a precipitation solvent, and then separating the solid from the liquid and drying to obtain a polymer of formula (Ic).
[0065] Preferably, the inorganic salt is a sodium salt and / or a potassium salt.
[0066] Preferably, the inorganic salt is at least one of sodium chloride, sodium sulfate, potassium chloride, potassium sulfate, sodium nitrate and sodium acetate.
[0067] Preferably, in step d), the temperature of the heat treatment is 50-90° C.; in step e), the acid solution is sulfuric acid solution.
[0068] The present invention also provides an application of the aromatic polymer proton exchange membrane described in the above technical solution in a fuel cell, hydrogen production by water electrolysis, a hydrogen pump or a liquid flow battery.
[0069] The proton exchange membrane prepared by the present invention uses a polyphenylfluoroketone polymer as a basic skeleton, introduces a fluorinated hydrophobic group for copolymerization, and sulfonates the bromofluoroketone chain to obtain a polyphenylfluoroketone PEM. On the one hand, the introduction of the fluorinated group improves the thermal stability, chemical resistance, glass transition temperature, etc. of the membrane, thereby improving the mechanical properties of the membrane; on the other hand, the introduction of the hydrophobic group and the side chain containing the sulfonic acid group form a microphase separation of the hydrophilic phase and the hydrophobic phase of the membrane, constructing a more efficient ion transmission channel, thereby improving the proton conductivity of the PEM. Moreover, in the polymer of formula (I), y / (x+y) is controlled to be 5% to 20%, so that the proton membrane has better performance under the above ratio. The proton exchange membrane obtained by the present invention has both high proton conductivity and good dimensional stability, and has good hydration swelling properties, which solves the problem that the current aromatic polymer proton exchange membrane cannot have both high conductivity and good dimensional stability under high temperature and high humidity conditions. It can be applied to a variety of electrocatalytic devices, such as fuel cells, water electrolysis hydrogen production, hydrogen pumps or liquid flow batteries.
[0070] The test results show that the water absorption rate of the proton exchange membrane obtained by the present invention at 30°C is above 25%, which is more than 1.2 times that of the commercial Nafion 212 membrane, and the water absorption rate at 80°C is above 35%, most of which are above 45%, and most of which are more than 1.3 times that of the commercial Nafion 212 membrane, which significantly improves the water absorption rate; at the same time, the swelling rate at 30°C is below 14%, and the swelling rate at 80°C is below 22%, which is relatively close to the commercial Nafion 212 membrane; therefore, the present invention exhibits good hydration swelling properties and still maintains a low swelling rate under high temperature and high humidity conditions. In addition, the proton exchange membrane obtained by the present invention has a proton conductivity of more than 62mS / cm at 30°C and a proton conductivity of more than 123mS / cm at 80°C when it is completely hydrated; wherein, the proton conductivity of the proton exchange membrane obtained by the scheme where the raw material type is within the preferred range in the above technical scheme is more than 108mS / cm at 30°C and more than 231mS / cm at 80°C, which is significantly higher than that of the commercial Nafion 212 membrane. In addition, the ion exchange capacity of the proton exchange membrane obtained by the present invention is more than 2meq / g, which is significantly higher than the electrochemical performance of the commercial Nafion 212 membrane. BRIEF DESCRIPTION OF THE DRAWINGS
[0071] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the provided drawings without paying creative work.
[0072] Figure 1 The NMR spectra of the precursor of formula (Ia), the intermediate of formula (Ib), and the product of formula (I-1) in Example 1;
[0073] Figure 2 The graph shows the proton conductivity test results of the proton exchange membrane obtained in Example 1 and the Nafion 212 commercial membrane in 30-80°C water. DETAILED DESCRIPTION
[0074] The present invention provides an aromatic polymer proton exchange membrane, wherein the membrane material is formed by an aromatic polymer represented by formula (I):
[0075]
[0076] in,
[0077] x and y are the molar percentages of the corresponding repeating units in the total repeating units; the repeating unit corresponding to x is a hydrophilic segment, and the repeating unit corresponding to y is a hydrophobic segment; x+y=100%.
[0078] y / (x+y)=5%~20%, that is, the proportion of the hydrophobic segment repeating unit corresponding to y to the total repeating unit is 5%~20%. If the proportion is too low, it is not conducive to the microscopic separation of the hydrophilic and hydrophobic phases in the structure, which is not conducive to the formation of a better ion transmission channel; if the proportion is too high, the proportion of the hydrophilic phase containing sulfonate groups decreases, resulting in a decrease in the IEC of the membrane, thereby reducing the proton conductivity of the membrane. The above proportions can be specifically 5%, 6%, 7%, 8%, 9%, 9%, 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19%, 20%.
[0079] n is the degree of polymerization, specifically, n≥10.
[0080] j is the number of methylene groups (-CH2-), selected from integers of 1 to 6, specifically 1, 2, 3, 4, 5, 6, preferably 5 or 6.
[0081] Ar is selected from any one of the structures of formula Ar1 to Ar6; more preferably, it is formula Ar1 or formula Ar5;
[0082]
[0083] R is a chain hydrocarbon group or a phenyl-containing structure, selected from any one of the structures of formula R1 to R3:
[0084]
[0085] In the above formula R1, p is the number of methylene groups (-CH2-), which is an integer selected from 0 to 6, specifically 0, 1, 2, 3, 4, 5, and 6.
[0086] In the present invention, preferably, the aromatic polymer is selected from formula (I-1) to formula (I-6):
[0087]
[0088] The aromatic polymer of formula (I) is a side chain type polyphenyl fluoroketone polymer. Taking formula (I-1) as an example, the aromatic polymer is a side chain type polybiphenyl fluoroketone polymer.
[0089] In the present invention, more preferably, the aromatic polymer is selected from the above formula (I-1), formula (I-2) or formula (I-6). In the present invention, more preferably, in the above formula (I-1), y / (x+y)=5%, 10% or 15%; in formulas (I-2) to (I-6), y / (x+y)=15%.
[0090] The present invention also provides a method for preparing the aromatic polymer proton exchange membrane described in the above technical solution, comprising the following steps:
[0091] a) reacting a precursor of formula (Ia) with potassium thioacetate to form an intermediate of formula (Ib);
[0092] b) mixing the intermediate of formula (Ib) with m-chloroperbenzoic acid and an inorganic salt to form a polymer of formula (Ic);
[0093] c) dissolving the polymer of formula (Ic) in a solvent to obtain a casting solution;
[0094] d) coating the casting solution on a substrate, and subjecting the substrate to a heat treatment to volatilize the solvent to obtain a thin film;
[0095] e) immersing the film in an acid solution to perform ion exchange, and then immersing it in water to remove excess acid solution to obtain a proton exchange membrane containing the aromatic polymer represented by formula (I);
[0096] in,
[0097] The structure of the precursor of formula (Ia) is as follows:
[0098]
[0099] The structure of the intermediate of formula (Ib) is as follows:
[0100]
[0101] The structure of the polymer of formula (Ic) is as follows:
[0102]
[0103] The structure of the aromatic polymer represented by formula (I) is as follows:
[0104]
[0105] In the above formula (Ia), formula (Ib), formula (Ic) and formula (I):
[0106] x and y are the molar percentages of the corresponding repeating units in the total repeating units; x+y=100%, and y / (x+y)=5% to 20%;
[0107] n is the degree of polymerization, n≥10;
[0108] j is an integer from 1 to 6;
[0109] Ar is selected from any one of the structures of formula Ar1 to Ar6:
[0110]
[0111] R is selected from any one of the structures of formula R1 to R3:
[0112]
[0113] In the above formula R1, p is an integer from 0 to 6;
[0114] In the formula (Ic), M is Na or K.
[0115] Regarding step a) :
[0116] a) reacting a precursor of formula (Ia) with potassium thioacetate to form an intermediate of formula (Ib).
[0117] In the present invention, the precursor of formula (Ia) is preferably prepared by the following preparation method: compound Ar', compound R' and compound C react to form the precursor of formula (Ia).
[0118] In the present invention, the compound Ar' is selected from any one of formulas Ar1' to Ar6', and more preferably is biphenyl represented by formula Ar1' or 3,3-dimethylbiphenyl represented by formula Ar5'. The present invention has no special restrictions on the source of the compound Ar', and it can be a commercial product or prepared according to a conventional preparation method known to those skilled in the art.
[0119]
[0120] In the present invention, the structure of the compound R' is shown in formula R', and more preferably is trifluoroacetophenone or trifluoroacetone. The present invention has no special restrictions on the source of the compound R', and it can be a commercial product or prepared according to conventional preparation methods known to those skilled in the art.
[0121]
[0122] Wherein, R is selected from any one of the structures of formula R1 to R3:
[0123]
[0124] In the above formula R1, p is an integer of 0 to 6, and specifically can be 0, 1, 2, 3, 4, 5, or 6.
[0125] In the present invention, the structure of the compound C is shown in Formula C. The present invention has no particular limitation on the source of the compound C, which may be a commercial product or prepared by a conventional preparation method known to those skilled in the art.
[0126]
[0127] Wherein, j is an integer of 1 to 6, specifically 1, 2, 3, 4, 5, 6, and more preferably 5 (i.e., 7-bromo-1,1,1-trifluoro-2-heptanone) or 6.
[0128] In the present invention, the molar ratio of compound Ar', compound R' and compound C is preferably 1:(0.04-0.14):(1.0-1.2).
[0129] In the present invention, the temperature for reacting compound Ar', compound R' and compound C is preferably 0-30°C, specifically 0°C, 5°C, 10°C, 15°C, 20°C, 25°C, 30°C.
[0130] In the present invention, the reaction is preferably carried out in an organic solvent medium. In the present invention, the organic solvent is preferably at least one of dichloromethane (DCM), dichloroethane, dichloropropane, trichloroethane, N,N-dimethylacetamide, tetrahydrofuran and ethyl acetate. In the present invention, the amount ratio of the compound Ar' to the organic solvent is preferably 0.7g: (2-4) mL, specifically 0.70g: 2 mL, 0.70g: 3 mL, 0.70g: 4 mL.
[0131] In the present invention, the preparation method of the precursor of formula (Ia) preferably specifically comprises:
[0132] S1, mixing compound Ar', compound R', compound C, an organic solvent and a catalyst, stirring and reacting at room temperature to obtain a gel;
[0133] S2. Pour the gel into an alcohol solvent to precipitate white fibers, then separate the solid and the liquid, dissolve the obtained solid in an organic solvent, precipitate it again with an alcohol solvent, then wash and dry to obtain a precursor of formula (Ia).
[0134] Regarding step S1:
[0135] The types and amounts of the compound Ar', compound R', compound C and organic solvent are the same as those described above and will not be described in detail here. The catalyst is preferably trifluoromethanesulfonic acid. The amount ratio of the catalyst to the compound Ar' is preferably (0.5-5) mL: 0.70 g.
[0136] The step S1 preferably specifically comprises: uniformly mixing compound Ar', compound R', compound C and an organic solvent, adding a catalyst, and stirring at room temperature for 6 to 48 hours to obtain a gel. Preferably, specifically, after adding the catalyst, stirring for 8 hours, observing that the reaction mixture becomes highly viscous, and then continuing to stir for 2 hours to obtain a dark brown gel-like substance.
[0137] Regarding step S2:
[0138] The alcohol solvent is preferably at least one of methanol, ethanol, isopropanol and n-propanol. The gel is slowly poured into the alcohol solvent to precipitate white fibers, and then solid-liquid separation is performed. In the present invention, the solid-liquid separation method is preferably vacuum filtration. After solid-liquid separation, a white fiber solid is obtained.
[0139] The obtained white fibrous solid is dissolved in an organic solvent. The organic solvent is preferably at least one of dichloromethane (DCM), dichloroethane, dichloropropane, trichloroethane, N,N-dimethylacetamide, tetrahydrofuran and ethyl acetate. The obtained solution is again put into an alcohol solvent for precipitation. The alcohol solvent is preferably at least one of methanol, ethanol, isopropanol and n-propanol. Then, preferably solid-liquid separation is also performed; the method of solid-liquid separation is preferably vacuum filtration. After solid-liquid separation, washing is performed. The washing liquid used for washing is preferably at least one of methanol, ethanol, isopropanol and n-propanol. After washing, drying is performed. The drying is preferably vacuum drying. The drying temperature is preferably 60 to 120°C. After drying, a white fibrous solid is obtained, i.e., the precursor of formula (Ia).
[0140] According to the present invention, after the precursor of formula (Ia) is obtained, the precursor of formula (Ia) is reacted with potassium thioacetate to sulfonate the bromine functional group in the precursor of formula (Ia) into a sulfonic acid group.
[0141] in;
[0142] The molar ratio of the potassium thioacetate (KSAc) to the precursor of formula (Ia) is preferably (1.1-1.6):1, specifically 1.2:1.
[0143] The reaction is preferably carried out in an organic solvent medium. The organic solvent is preferably N,N-dimethylacetamide (DMAc). The ratio of the organic solvent to the precursor of formula (Ia) is preferably (15-25) mL: 1 g, specifically 20 mL: 1 g.
[0144] The reaction temperature is preferably 50-100° C., specifically 50° C., 60° C., 70° C., 80° C., 90° C., 100° C. The reaction time is preferably 4-6 hours, specifically 4 hours, 5 hours, 6 hours. After the above reaction, the precursor of formula (Ia) is formed in the system.
[0145] In the present invention, the step a) preferably specifically comprises:
[0146] a1) reacting a precursor of formula (Ia) with potassium thioacetate and an organic solvent to obtain a reaction solution;
[0147] a2) Post-treatment: The reaction solution is put into an alcohol solvent for precipitation, followed by solid-liquid separation. Thereafter, the obtained solid-liquid is dissolved in an organic solvent, and then precipitated again with an alcohol solvent and solid-liquid separated to obtain the intermediate of formula (Ib).
[0148] Regarding step a1):
[0149] The types of substances and amounts used are consistent with those described above and will not be repeated here.
[0150] Regarding step a2):
[0151] Before alcohol precipitation, the reaction solution is preferably cooled to room temperature. The alcohol solvent is preferably at least one of methanol, ethanol, isopropanol and n-propanol. The gel is poured into the alcohol solvent, precipitated, and then solid-liquid separation is performed. In the present invention, the solid-liquid separation method is preferably vacuum filtration. After solid-liquid separation, a solid is obtained. The obtained solid is dissolved in an organic solvent. The organic solvent is preferably at least one of tetrahydrofuran (THF), dichloromethane, N,N-dimethylacetamide (DMAc) and chloroform. The obtained solution is again put into an alcohol solvent for precipitation. The alcohol solvent is preferably at least one of methanol, ethanol, isopropanol and n-propanol. Then, solid-liquid separation is preferably performed; the solid-liquid separation method is preferably vacuum filtration. After solid-liquid separation, drying is performed. The drying is preferably vacuum drying. The drying temperature is preferably 60 to 120°C. After drying, the intermediate of formula (Ib) is obtained.
[0152] Regarding step b) :
[0153] b) mixing the intermediate of formula (Ib) with m-chloroperbenzoic acid and an inorganic salt to form a polymer of formula (Ic).
[0154] In the present invention, the step b) preferably specifically comprises:
[0155] b1) dissolving the intermediate of formula (Ib) in an organic solvent to obtain a solution;
[0156] b2) after cooling the dissolved solution, adding m-chloroperbenzoic acid, then returning to the temperature and stirring evenly to obtain a solution;
[0157] b3) mixing the solution obtained in step b2) with an inorganic salt solution, and then performing solid-liquid separation and washing to obtain a solid;
[0158] b4) dissolving the solid in an organic solvent, precipitating with a precipitation solvent, and then separating the solid from the liquid and drying to obtain a polymer of formula (Ic).
[0159] Regarding step b1):
[0160] The organic solvent is preferably at least one of N,N-dimethylacetamide and N,N-dimethylformamide. The ratio of the organic solvent to the intermediate of formula (Ib) is preferably (15-20) mL: 0.9 g, specifically 18 mL: 0.9 g. The dissolving temperature in step b1) is not particularly limited, and can be carried out at room temperature, which can be 15-35°C, specifically 15°C, 20°C, 25°C, 30°C, 35°C.
[0161] Regarding step b2):
[0162] The cooling is preferably cooled to -1°C to 5°C, specifically -1°C, 0°C, 1°C, 2°C, 3°C, 4°C, 5°C. The molar ratio of the meta-chloroperbenzoic acid (mCPBA) to the intermediate of formula (Ib) is preferably ≥3:1. Commercial meta-chloroperbenzoic acid commercial products are usually solutions of meta-chloroperbenzoic acid dissolved in a solvent. In the present invention, the purity of the meta-chloroperbenzoic acid raw material liquid is preferably 70% to 75%. When adding the meta-chloroperbenzoic acid raw material, it is preferably added in batches. After the meta-chloroperbenzoic acid is completely added, the temperature is returned to room temperature; the present invention preferably returns to room temperature, which can be 15 to 30°C, specifically 15°C, 20°C, 25°C, 30°C. After returning to temperature, stirring is performed, and the stirring time is preferably 3 to 6h, specifically 3h, 4h, 5h, 6h. After stirring evenly, a solution is obtained.
[0163] Regarding step b3):
[0164] The inorganic salt in the inorganic salt solution is preferably a sodium salt and / or a potassium salt, more preferably at least one of sodium chloride, sodium sulfate, potassium chloride, potassium sulfate, sodium nitrate and sodium acetate. The concentration of the inorganic salt solution is preferably 1-2M, specifically 1M. The dosage ratio of the inorganic salt solution to the intermediate of formula (Ib) is preferably (50-100) mL: 0.9 g, more preferably 50 mL: 0.9 g. The method of mixing the solution obtained in step b2) with the inorganic salt solution is preferably stirring and mixing; the temperature conditions are not particularly limited, and can be carried out at room temperature, which can be 15-35°C, specifically 15°C, 20°C, 25°C, 30°C, 35°C; the stirring time is preferably 1-2h, specifically 1h, 1.5h, 2h. After the above mixing, solid-liquid separation and washing are carried out. Among them, the method of solid-liquid separation is not particularly limited, and it can be a conventional solid-liquid separation operation in the field, such as filtration. The washing is preferably washed with clean water. After washing, solids. The intermediate of formula (Ib) is converted into a polymer in the form of a salt by reaction in step b3).
[0165] Regarding step b4):
[0166] The organic solvent is preferably at least one of dimethyl sulfoxide (DMSO) and N,N-dimethylacetamide (DMAc). The amount ratio of the organic solvent to the intermediate of formula (Ib) is preferably (6-15) mL: 0.9 g, specifically 10 mL: 0.9 g. After the solid obtained in step b3) is dissolved in an organic solvent to obtain a solution, a precipitation solvent is used to precipitate; specifically, the solution is also mixed with a precipitation solvent, so that a precipitate is precipitated in the mixed liquid system. The precipitation solvent is preferably at least one of acetone, butanone, ether and toluene. The volume ratio of the precipitation solvent to the organic solvent is preferably (3-8) : 1, specifically 5: 1. After the above precipitation operation, solid-liquid separation and drying are performed. Among them, the method of solid-liquid separation is not particularly limited, and it can be a conventional solid-liquid separation operation in the field, such as filtration. The drying is preferably vacuum drying. The drying temperature is preferably 60-120°C. After drying, a polymer of formula (Ic) is obtained.
[0167] Regarding step c) :
[0168] c) dissolving the polymer of formula (Ic) in a solvent to obtain a casting solution.
[0169] In the present invention, the solvent is preferably at least one of dimethyl sulfoxide and N,N-dimethylacetamide. The dosage ratio of the polymer of formula (Ic) to the solvent is preferably 0.15g: (5-25) mL, specifically 0.15g: 10 mL. The method of dissolving the polymer of formula (Ic) in the solvent is preferably stirring and dissolving. The temperature of the stirring and dissolving is preferably 25-80°C, specifically 25°C, 30°C, 35°C, 40°C, 45°C, 50°C, 55°C, 60°C, 65°C, 70°C, 75°C, 80°C; the stirring time is preferably 5-20h, specifically 12h. After the above treatment, a uniform casting solution is obtained.
[0170] Regarding step d) :
[0171] d) coating the casting solution on a substrate, and subjecting the substrate to heat treatment to evaporate the solvent to obtain a thin film.
[0172] In the present invention, the type of the substrate is not particularly limited, and it can be a commonly used substrate for preparing proton exchange membranes in the art, such as a glass plate. The temperature of the heat treatment is preferably 50 to 90°C, specifically 50°C, 55°C, 60°C, 65°C, 70°C, 75°C, 80°C, 85°C, 90°C; the solvent in the casting solution is evaporated by the heat treatment, thereby forming a transparent film on the substrate. After the above treatment, the film is peeled off from the substrate to obtain a film.
[0173] Regarding step e) :
[0174] e) immersing the membrane in an acid solution to perform ion exchange, and then immersing it in water to remove excess acid solution, thereby obtaining a proton exchange membrane containing the aromatic polymer represented by formula (I).
[0175] In the present invention, the acid solution is preferably sulfuric acid solution. The concentration of the acid solution is preferably 1 to 2 M, specifically 1 M, 1.5 M, or 2 M. In the present invention, the film is immersed in the acid solution for preferably 20 to 30 hours, specifically 24 hours. During the above immersion process, ion exchange occurs, and the metal salt ions in the polymer of formula (Ic) are exchanged into H + . After the above ion exchange, the membrane is preferably washed with deionized water. After the above washing, the membrane is immersed in water to remove excess acid; the immersion time is preferably 20 to 36 hours, specifically 24 hours. After the above treatment, an acidified aromatic polymer proton exchange membrane is obtained, that is, a proton exchange membrane containing an aromatic polymer represented by formula (I).
[0176] In the present invention, the thickness of the proton exchange membrane is preferably 15 to 80 μm, specifically 40 μm.
[0177] The present invention also provides an application of the aromatic polymer proton exchange membrane described in the above technical solution in a fuel cell, hydrogen production by water electrolysis, a hydrogen pump or a liquid flow battery.
[0178] The proton exchange membrane prepared by the present invention uses a polyphenylfluoroketone polymer as a basic skeleton, introduces a fluorinated hydrophobic group for copolymerization, and sulfonates the bromofluoroketone chain to obtain a polyphenylfluoroketone PEM. On the one hand, the introduction of the fluorinated group improves the thermal stability, chemical resistance, glass transition temperature, etc. of the membrane, thereby improving the mechanical properties of the membrane; on the other hand, the introduction of the hydrophobic group and the side chain containing the sulfonic acid group form a microphase separation of the hydrophilic phase and the hydrophobic phase of the membrane, constructing a more efficient ion transmission channel, thereby improving the proton conductivity of the PEM. Moreover, in the polymer of formula (I), y / (x+y) is controlled to be 5% to 20%, so that the proton membrane has better performance under the above ratio. The proton exchange membrane obtained by the present invention has both high proton conductivity and good dimensional stability, and has good hydration swelling, which solves the problem that the current aromatic polymer proton exchange membrane cannot have both high conductivity and dimensional stability. It can be applied to a variety of electrocatalytic devices, such as fuel cells, water electrolysis hydrogen production, hydrogen pumps or liquid flow batteries.
[0179] The test results show that the water absorption rate of the proton exchange membrane obtained by the present invention at 30°C is above 25%, which is more than 1.2 times that of the commercial Nafion 212 membrane, and the water absorption rate at 80°C is above 35%, most of which are above 45%, and most of which are more than 1.3 times that of the commercial Nafion 212 membrane, which significantly improves the water absorption rate; at the same time, the swelling rate at 30°C is below 14%, and the swelling rate at 80°C is below 22%, which is relatively close to the commercial Nafion 212 membrane; therefore, the present invention exhibits good hydration swelling properties and still maintains a low swelling rate under high temperature and high humidity conditions. In addition, the proton exchange membrane obtained by the present invention has a proton conductivity of more than 62mS / cm at 30°C and a proton conductivity of more than 123mS / cm at 80°C when it is completely hydrated; wherein, the proton conductivity of the proton exchange membrane obtained by the scheme where the raw material type is within the preferred range in the above technical scheme is more than 108mS / cm at 30°C and more than 231mS / cm at 80°C, which is significantly higher than that of the commercial Nafion 212 membrane. In addition, the ion exchange capacity of the proton exchange membrane obtained by the present invention is more than 2meq / g, which is significantly higher than the electrochemical performance of the commercial Nafion 212 membrane.
[0180] In order to further understand the present invention, preferred embodiments of the present invention are described below in conjunction with examples. However, it should be understood that these descriptions are only for further illustrating the features and advantages of the present invention, rather than limiting the claims of the present invention.
[0181] Example 1
[0182] 1. Preparation of the precursor of formula (Ia):
[0183] S1. Dissolve 0.70 g of biphenyl, 0.103 g of trifluoroacetophenone and 1.19 g of 7-bromo-1,1,1-trifluoro-2-heptanone in 3 mL of dichlorohexane and mix well. Then, add 3 mL of trifluoromethanesulfonic acid and stir at room temperature for 8 h. Observe that the reaction mixture becomes highly viscous and continue stirring for 2 h to obtain a dark brown gel.
[0184] S2. The obtained gel is slowly poured into methanol to precipitate white fibers, which are then vacuum filtered. The obtained white fiber solid is dissolved in dichloromethane, and then put into methanol again to precipitate solids. After filtering, the solids are washed and vacuum dried to obtain a white fiber-like solid, i.e., the precursor of formula (Ia), having the following structure:
[0185]
[0186] Wherein, y / (x+y)=15%, j=5, and R is phenyl.
[0187] 2. Preparation of intermediate of formula (Ib):
[0188] a1) In a single-diameter round-bottom flask, 1.00 g of the precursor of formula (Ia), 0.33 g of potassium thioacetate and 20 mL of N,N-dimethylacetamide were added, and the mixture was heated to 50° C. in an oil bath for 5 h to obtain a reaction solution.
[0189] a2) The reaction solution is cooled to room temperature, added to 100 mL of methanol to precipitate, and then vacuum filtered; thereafter, the obtained solid is dissolved in 10 mL of tetrahydrofuran, and the solution is again added to 100 mL of methanol to precipitate, and then vacuum filtered and vacuum dried to obtain the intermediate of formula (Ib).
[0190] 3. Preparation of polymer of formula (Ic):
[0191] b1) Add 0.90 g of the intermediate of formula (Ib) and 18 mL of N,N-dimethylacetamide into a 100 mL double-layer bottle and dissolve them uniformly to obtain a solution.
[0192] b2) The dissolved solution was cooled to 0°C, and meta-chloroperbenzoic acid raw material solution (purity 75%, molar ratio of meta-chloroperbenzoic acid to the intermediate of formula (Ib) 3:1) was added in stages. After the addition was completed, the solution was warmed to room temperature and stirred for 5 hours to obtain a solution.
[0193] b3) The solution obtained in step b2) was added to a sodium chloride solution (50 mL, concentration 1 M), stirred for 1.5 h, filtered and washed three times with clean water to obtain a solid.
[0194] b4) The obtained solid was dissolved in 10 mL of dimethyl sulfoxide, and then put into 50 mL of acetone to precipitate, which was filtered and dried in vacuo to obtain a polymer of formula (Ic).
[0195] 4. Preparation of proton exchange membrane:
[0196] c) Add 0.15 g of the polymer of formula (Ic) into 10 mL of dimethyl sulfoxide and stir for 12 h to obtain a uniform casting solution.
[0197] d) The casting solution is coated on a clean and flat glass plate, heated to 80° C. to evaporate the dimethyl sulfoxide solvent to form a transparent film, and then peeled off from the glass plate to obtain a film.
[0198] e) Immersing the film in H2SO4 solution (concentration 1M) for ion exchange, after immersing for 24 hours, washing the H2SO4 with deionized water, and immersing the film in deionized water for 24 hours to ensure removal of residual H2SO4, thereby obtaining an acidified side-chain polybiphenyl fluoroketone proton exchange membrane, i.e., a proton exchange membrane containing an aromatic polymer represented by formula (I) (thickness of about 40 μm).
[0199] The structure of the aromatic polymer of formula (I) is shown in formula (I-1):
[0200]
[0201] Wherein, y / (x+y)=15%, and the product of the above formula (I-1) is recorded as BPSA-PT15%.
[0202] The individual intermediates and products in the above preparation process were characterized by NMR spectra, and the results were as follows: Figure 1 As shown, Figure 1 The NMR spectra of the precursor of formula (Ia), the intermediate of formula (Ib), and the product of formula (I-1) in Example 1.
[0203] Example 2
[0204] The process was carried out in accordance with Example 1, except that in the process of preparing the precursor of formula (Ia) in step 1, the amount of trifluoroacetophenone was adjusted to 0.0343 g, and the amount of 7-bromo-1,1,1-trifluoro-2-heptanone was adjusted to 1.28 g.
[0205] In the proton exchange membrane finally obtained, the structure of the aromatic polymer of formula (I) is shown in formula (I-1):
[0206]
[0207] Among them, y / (x+y)=5%.
[0208] Example 3
[0209] The process was carried out in accordance with Example 1, except that in the process of preparing the precursor of formula (Ia) in step 1, the amount of trifluoroacetophenone was adjusted to 0.0687 g, and the amount of 7-bromo-1,1,1-trifluoro-2-heptanone was adjusted to 1.262 g.
[0210] In the proton exchange membrane finally obtained, the structure of the aromatic polymer of formula (I) is shown in formula (I-1):
[0211]
[0212] Among them, y / (x+y)=10%.
[0213] Example 4
[0214] The method is carried out in accordance with Example 1, except that in the process of preparing the precursor of formula (Ia) in step 1, biphenyl is replaced by an equimolar amount of m-terphenyl.
[0215] In the proton exchange membrane finally obtained, the structure of the aromatic polymer of formula (I) is shown in formula (I-3):
[0216]
[0217] Among them, y / (x+y)=15%.
[0218] Example 5
[0219] The method was carried out in accordance with Example 1, except that, in the process of preparing the precursor of formula (Ia) in step 1, trifluoroacetophenone was replaced by an equimolar amount of trifluoroacetone.
[0220] In the proton exchange membrane finally obtained, the structure of the aromatic polymer of formula (I) is shown in formula (I-2):
[0221]
[0222] Among them, y / (x+y)=15%.
[0223] Example 6
[0224] The process is carried out in accordance with Example 1, except that in the process of preparing the precursor of formula (Ia) in step 1, 7-bromo-1,1,1-trifluoro-2-heptanone is replaced by an equimolar amount of 5-bromo-1,1,1-trifluoro-2-pentanone.
[0225] In the proton exchange membrane finally obtained, the structure of the aromatic polymer of formula (I) is shown in formula (I-4):
[0226]
[0227] Among them, y / (x+y)=15%.
[0228] Example 7
[0229] The process is carried out in accordance with Example 1, except that in the process of preparing the precursor of formula (Ia) in step 1, 7-bromo-1,1,1-trifluoro-2-heptanone is replaced by an equimolar amount of 6-bromo-1,1,1-trifluoro-2-hexanone.
[0230] In the proton exchange membrane finally obtained, the structure of the aromatic polymer of formula (I) is shown in formula (I-5):
[0231]
[0232] Among them, y / (x+y)=15%.
[0233] Example 8
[0234] The method was carried out in accordance with Example 1, except that in the process of preparing the precursor of formula (Ia) in step 1, biphenyl was replaced by an equimolar amount of 3,3-dimethylbiphenyl.
[0235] In the proton exchange membrane finally obtained, the structure of the aromatic polymer of formula (I) is shown in formula (I-6):
[0236]
[0237] Among them, y / (x+y)=15%.
[0238] Example 9: Product Testing
[0239] The proton conductivity, water absorption and swelling rate of the proton exchange membrane in water at 30-80°C were tested respectively, as well as the ion exchange capacity of the proton exchange membrane; the above tests refer to the national standard GB / T 20042.3-2022. The above tests were performed on the proton exchange membranes obtained in Examples 1-8 and the Nafion 212 commercial membrane, and the test results are shown in Table 1.
[0240] Table 1: Product performance
[0241]
[0242] The proton conductivity of the proton exchange membrane obtained in Example 1 and the commercial Nafion 212 membrane in water at 30 to 80°C is as follows: Figure 2 As shown, Figure 2 The graph is a test result of the proton conductivity of the proton exchange membrane obtained in Example 1 and the commercial Nafion 212 membrane in 30-80° C. water. It can be seen that under the condition of 30-80° C., the proton conductivity of the proton exchange membrane obtained in Example 1 is always higher than that of the commercial Nafion 212 membrane.
[0243] It can be seen from the test results in Table 1 that the water absorption rate of the proton exchange membranes obtained in Examples 1-8 of the present invention at 30°C is above 25%, which is more than 1.2 times that of the Nafion 212 commercial membrane, and the water absorption rate at 80°C is above 35%, most of which is above 45%, and most of which is more than 1.3 times that of the Nafion 212 commercial membrane, which significantly improves the water absorption rate; at the same time, the swelling rate at 30°C is below 14%, and the swelling rate at 80°C is below 22%, which is relatively close to the Nafion 212 commercial membrane; therefore, Examples 1-8 show good hydration swelling properties and still maintain a low swelling rate under high temperature and high humidity conditions. In addition, the proton exchange membranes obtained in Examples 1-8 have a proton conductivity of more than 62 ms / cm at 30°C and a proton conductivity of more than 123 ms / cm at 80°C when fully hydrated; wherein the proton exchange membranes obtained in the schemes where the raw material types are within the preferred range of the above technical schemes (corresponding to Examples 1-3, 5, and 8) have a proton conductivity of more than 108 ms / cm at 30°C and a proton conductivity of more than 231 ms / cm at 80°C, which are significantly higher than the commercial membrane Nafion 212. In addition, the ion exchange capacity of the proton exchange membranes obtained in Examples 1-8 is more than 2 meq / g, which is significantly higher than the electrochemical performance of the commercial membrane Nafion 212.
[0244] Specific examples are used herein to illustrate the principles and implementation methods of the present invention. The description of the above embodiments is only used to help understand the method of the present invention and its core ideas, including the best mode, and also enable any technician in the field to practice the present invention, including making and using any device or system, and implementing any combined method. It should be pointed out that for ordinary technicians in this technical field, without departing from the principle of the present invention, the present invention can also be improved and modified, and these improvements and modifications also fall within the scope of protection of the claims of the present invention. The scope of patent protection of the present invention is defined by the claims and may include other embodiments that can be thought of by those skilled in the art. If these other embodiments have structural elements similar to the literal expression of the claims, or if they include equivalent structural elements that are not substantially different from the literal expression of the claims, then these other embodiments should also be included in the scope of the claims.
Claims
1. An aromatic polymer proton exchange membrane, characterized in that The membrane material is formed from an aromatic polymer represented by formula (I): The method for preparing the aromatic polymer proton exchange membrane comprises the following steps: a) reacting a precursor of formula (Ia) with potassium thioacetate to form an intermediate of formula (Ib); b) mixing the intermediate of formula (Ib) with m-chloroperbenzoic acid and an inorganic salt to form a polymer of formula (Ic); the inorganic salt is a sodium salt and / or a potassium salt; c) dissolving the polymer of formula (Ic) in a solvent to obtain a casting solution; d) coating the casting solution on a substrate, and subjecting the substrate to heat treatment to volatilize the solvent to obtain a thin film; the heat treatment temperature is 50 to 90° C.; e) immersing the film in an acid solution to perform ion exchange, and then immersing it in water to remove excess acid solution, thereby obtaining a proton exchange membrane containing the aromatic polymer represented by formula (I); the acid solution is sulfuric acid solution; In step a), the precursor of formula (Ia) is prepared by the following preparation method: compound Ar', compound R' and compound C react to form a precursor of formula (Ia); The compound Ar' is selected from any one of the formulas Ar1' to Ar6': The structure of the compound R' is shown in formula R': The structure of the compound C is shown in Formula C: Wherein, j is an integer from 1 to 6; The structure of the precursor of formula (Ia) is as follows: The structure of the intermediate of formula (Ib) is as follows: The structure of the polymer of formula (Ic) is as follows: in, x, y are the molar percentages of the corresponding repeating units to all repeating units; x+y=100%, and y / (x+y)=5%~20%; n is the degree of polymerization, n≥10; j is an integer from 1 to 6; Ar is selected from any one of the structures of formula Ar1 to Ar6: R is selected from any one of the structures of formula R1 to R3: In the above formula R1, p is an integer of 0-6.
2. The proton exchange membrane according to claim 1, characterized in that The aromatic polymer is selected from formula (I-1) to formula (I-6):
3. A method for preparing an aromatic polymer proton exchange membrane according to any one of claims 1 to 2, characterized in that: The following steps are involved: a) reacting a precursor of formula (Ia) with potassium thioacetate to form an intermediate of formula (Ib); b) mixing the intermediate of formula (Ib) with m-chloroperbenzoic acid and an inorganic salt to form a polymer of formula (Ic); the inorganic salt is a sodium salt and / or a potassium salt; c) dissolving the polymer of formula (Ic) in a solvent to obtain a casting solution; d) coating the casting solution on a substrate, and subjecting the substrate to heat treatment to volatilize the solvent to obtain a thin film; the heat treatment temperature is 50 to 90° C.; e) immersing the film in an acid solution to perform ion exchange, and then immersing it in water to remove excess acid solution, thereby obtaining a proton exchange membrane containing the aromatic polymer represented by formula (I); the acid solution is sulfuric acid solution; In step a), the precursor of formula (Ia) is prepared by the following preparation method: compound Ar', compound R' and compound C react to form a precursor of formula (Ia); The compound Ar' is selected from any one of the formulas Ar1' to Ar6': The structure of the compound R' is shown in formula R': The structure of the compound C is shown in Formula C: Wherein, j is an integer from 1 to 6; in, The structure of the precursor of formula (Ia) is as follows: The structure of the intermediate of formula (Ib) is as follows: The structure of the polymer of formula (Ic) is as follows: In formula (Ic): M is Na or K; The structure of the polymer represented by formula (I) is as follows: In the above formula (Ia), formula (Ib), formula (Ic) and formula (I): x and y are the molar percentages of the corresponding repeating units in the total repeating units; x+y=100%, and y / (x+y)=5% to 20%; n is the degree of polymerization, n≥10; j is an integer from 1 to 6; Ar is selected from any one of the structures of formula Ar1 to Ar6: R is selected from any one of the structures of formula R1 to R3: In the above formula R1, p is an integer from 0 to 6; In the formula (Ic), M is Na or K.
4. The preparation method according to claim 3, characterized in that: The step a) specifically comprises: a1) reacting a precursor of formula (Ia) with potassium thioacetate and an organic solvent to obtain a reaction solution; a2) Post-treatment: The reaction solution is put into an alcohol solvent for precipitation, followed by solid-liquid separation. Thereafter, the obtained solid-liquid is dissolved in an organic solvent, and then precipitated again with an alcohol solvent and solid-liquid separated to obtain the intermediate of formula (Ib).
5. The preparation method according to claim 3, characterized in that: The step b) specifically comprises: b1) dissolving the intermediate of formula (Ib) in an organic solvent to obtain a solution; b2) after cooling the dissolved solution, adding m-chloroperbenzoic acid, then returning to the temperature and stirring evenly to obtain a solution; b3) mixing the solution obtained in step b2) with an inorganic salt solution, and then performing solid-liquid separation and washing to obtain a solid; b4) dissolving the solid in an organic solvent, precipitating with a precipitation solvent, and then separating the solid from the liquid and drying to obtain a polymer of formula (Ic).
6. The preparation method according to claim 3, characterized in that: The inorganic salt is at least one of sodium chloride, sodium sulfate, potassium chloride, potassium sulfate, sodium nitrate and sodium acetate.
7. Use of the aromatic polymer proton exchange membrane according to any one of claims 1 to 2 in a fuel cell, hydrogen production by water electrolysis, a hydrogen pump or a liquid flow battery.
Citation Information
Patent Citations
Grafted polymer proton exchange membrane and preparation method thereof
CN104835933A
Proton exchange membrane with polymer main chain of aromatic ring structure and preparation method thereof
CN113150344A